Material Comparative Study of 4 Stage Gear Box Housing Using Fea Methodology - et. al., N.Elumalai, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The material comparative study of the product is used to reduce the weight of the product and then structural strength improvement, four stage gear box mostly used in the light vehicles like car and small Omni vehicles, gear box is the component give the more weight in the vehicle, gear box weight reduction and structural stability can be analyze through FEA methodology in ANSYS software